Nucleation of plasticity in nanoparticle collisions - Millán, Emmanuel Nicolás (2016)
While at small collision velocities collisions of nanoparticles (NPs) are elastic, they become plastic at higher velocities. We study the elastic-plastic threshold and the onset of plasticity using molecular dynamics simulation for a Lennard-Jones material. The reasons behind the R-2/3 increase of the threshold velocity for small NP radii R found recently are discussed. At the threshold, NP orientation strongly influences the generation of plasticity, and averaging over many orientations is required to predict the critical velocity for dislocation generation. The onset of plasticity is governed by the generation of isolated stacking faults and nanotwins spanning the entire NP. At higher velocities, the fraction of defects becomes proportional to the total number of atoms in the NP.